A Long Story of Sensitized One‐Electron Photo‐oxidation of Methionine. Issue 3 (3rd March 2014) - Ignasiak, Marta Teresa; Marciniak, Bronislaw; Houée‐Levin, Chantal
Abstract The one‐electron oxidation of methionine residues in peptides and proteins has been studied for more than 20 years thanks to the time‐resolved techniques of pulse radiolysis and flash photolysis. Methionine oxidation causes highly damaging effects associated with aging processes and disease states such as Alzheimer's or prion disease and cerebral amyloid angiopathy. In this Minireview, we focus on the photoinduced processes that help in the understanding of the primary processes of methionine residue oxidation. The photosensitizers were mostly derivatives of carboxybenzophenone. The methionine radical cations are stabilized by two‐center three‐electron bonds of various natures. However, despite numerous studies, data about the final product are still missing.